Pengembangan Bola Karet Alat Pengukur Kekuatan Otot Tangan - Eny Erlinda Widyaastuti; Erni Chaerani; Husman Husman; Eko Yudo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to test the right rubber ball for measuring hand muscle strength. This research method was carried out using a quasi-experimental design. The results showed that the value of count (Pearson Product Moment Correlation) > r-table was 0.176. The reliability test results on the three right and left-hand measuring instruments were > 0.6 with a Cronbah's Alpha value of 0.920 > 0.6. In conclusion, testing the validity and reliability of rubber balls on muscle strength measuring devices with sizes of 7 cm, 8 cm, and 9 cm, which was carried out involving 130 respondents, showed valid and statistically reliable results. Keywords: Rubber ball, Hand Muscle Strength, Clinical Assessment